The Application of Long-Jump Variations Based on Macromedia Flash for Students of Sports Training Education in the Faculty of Sport Science, Universitas Negeri Medan 2022 - Yan Indra Siregar; Irwansyah Siregar; Indra Darma Sitepu (Randwick International of Social Science Journal, 2022)
This study aims to improve the quality of learning and learning outcomes of students of Sports Coaching Education, especially at the State University of Medan, Faculty of Sports Science. This research will produce a learning product that is combined with technology so that it can facilitate the implementation of higher quality learning. The research used in this study is experimental, meaning that research that aims to find a quality or causal relationship with the research design used in this study is a one group pretest-posttest design. The results of the study obtained the value of Sig. (2-tailed) is 0.000 while when compared with a significance level of 0.05, the results obtained from the conclusions of the paired test are: The significance value (2-tailed) <0.05 indicates a significant increase between the initial variable and the final variable. This shows that there is a significant increase in the difference in treatment given to each variable. So it was concluded that the significance value of 0.000 < 0.05 there was an increase in the application of long-jump variations based on macromedia flash for students of sports training education in the faculty of sport science, Universitas Negeri Medan 2022. It is very significant in the application of learning using digital media students experience changes in behavior because students are more confident, easily/quickly understand the long jump variation, so that the development of student learning abilities will increase and be able to think more critically (High Order Thinking Skill)